2007
DOI: 10.1111/j.1440-1746.2007.05103.x
|View full text |Cite
|
Sign up to set email alerts
|

Lamivudine/pegylated interferon alfa‐2b sequential combination therapy compared with lamivudine monotherapy in HBeAg‐negative chronic hepatitis B

Abstract: Sequential combination treatment is able to improve sustained biochemical response rates and prevent the emergence of lamivudine-resistant mutants in patients with HBeAg-negative chronic hepatitis B.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…In a 3-year follow-up of the HBeAg-negative patients, one third of those treated with peginterferon had maintained normal ALT levels and HBV DNA levels of \10,000 copies/ml [8]. Similar findings have been reported in studies of peginterferon alfa-2b in patients with HBeAgpositive [15,16] and HBeAg-negative CHB [17,18].…”
Section: Peginterferon Alfasupporting
confidence: 82%
“…In a 3-year follow-up of the HBeAg-negative patients, one third of those treated with peginterferon had maintained normal ALT levels and HBV DNA levels of \10,000 copies/ml [8]. Similar findings have been reported in studies of peginterferon alfa-2b in patients with HBeAgpositive [15,16] and HBeAg-negative CHB [17,18].…”
Section: Peginterferon Alfasupporting
confidence: 82%
“…In spite of high rate of drug resistance, so far, lamivudine is the most widely used nucleoside analogues for HBV treatment owing to its low price, safety and effectiveness [30]. Many previous studies reported that a combination of IFN-α and lamivudine achieved some therapeutic effects [31,32]. Here, in comparison to the treatment with exogenously added hIFN-α combined with lamivudine, the combination of endogenously expressed hIFN-α and lamivudine could restrain HBV more effectively at a certain degree (Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…There was no interruption in LAM therapy before randomization. We chose a 3:1 ratio for patient assignment on the basis of preliminary data, suggesting that interferon/LAM combination treatment is more effective than LAM monotherapy and delays the development of LAM resistance 23,24 . We extrapolated that ADV/LAM combination would also be superior to LAM monotherapy, and therefore, opted to treat most patients with ADV plus LAM.…”
Section: Methodsmentioning
confidence: 99%